Genome-Wide Identification and Characterization of APETALA2/Ethylene-Responsive Element Binding Factor Superfamily Genes in Soybean Seed Development - Jiang, Wenbo; Zhang, Xuejing; Song, Xuewei; Yang, Junfeng; Pang, Yongzhen (Frontiers in Plant Science, 2020)
Glycine max is one of the most important grain and oil crops, and improvement of seed yield is one of the major objectives in soybean breeding. The AP2/ERF superfamily members are involved in regulating flower and seed development in many species, and therefore play key roles in seed yield. However, it is still unknown that how many AP2/ERF members were presented in the G. max genome and whether these AP2/ERF family members function in flower and seed development in G. max. Here, we identified 380 AP2/ERF superfamily genes in the G. max genome. Phylogenetic analysis showed that 323 members were grouped into the ERF family, and 49 into the AP2 family. Among the AP2 family, 14 members of the euAP2 lineage showed high identity with their orthologs, and eight member of the ANT lineage were expressed highly in the seeds. Furthermore, seven of them (GmAP2-1 to GmAP2-7) were successfully cloned and over-expressed in Arabidopsis thaliana. The transgenic Arabidopsis plants over-expressing these GmAP2 genes flowered earlier relative to the wild type control. The seed length and width, and seed area of these over-expression lines were increased compared with the wild type, and seed weight of over-expression lines of GmAP2-1, GmAP2-4, GmAP2-5, and GmAP2-6 were greater than those of the wild type. Furthermore, the seed number per silique of the over-expression lines for GmAP2 genes were not affected except GmAP2-5. Collectively, GmAP2-1, GmAP2-4, and GmAP2-6 played important roles in regulating seed weight by affecting seed length, width and area, and further controlling seed yield.